Neuronal activity modulates alpha-synuclein aggregation and spreading in organotypic brain slice cultures and in vivo - Wu, Qihui; Shaikh, Muhammad A.; Meymand, Emily S.; Zhang, Bin; Luk, Kelvin C.; Trojanowski, John Q.; Lee, Virginia M.-Y. (Acta neuropathologica, 2020)
Alpha-synuclein (αSyn) preformed fibrils (PFF) induce endogenous αSyn aggregation leading to reduced synaptic transmission. Neuronal activity modulates release of αSyn; however, whether neuronal activity regulates the spreading of αSyn pathology remains elusive. Here, we established a hippocampal slice culture system from wild-type (WT) mice and found that both Ca 2+ influx and the uptake of αSyn PFF were higher in the CA3 than in the CA1 sub-region. Pharmacologically enhancing neuronal activity substantially increased αSyn pathology in αSyn PFF-treated hippocampal or midbrain slice cultures and accelerated dopaminergic neuron degeneration. Consistently, neuronal hyperactivity promoted PFF trafficking along axons/dendrites within microfluidic chambers. Unexpectedly, enhancing neuronal activity in LRRK2 G2019S mutant slice cultures further increased αSyn pathology, especially with more Lewy body (LB) forming than in WT slice cultures. Finally, following injection of αSyn PFF and chemogenetic modulators into the dorsal striatum of WT mice, both motor behavior and αSyn pathology were exacerbated likely by enhancing neuronal activity, since they were ameliorated by reducing neuronal activity. Thus, a greater understanding of the impact of neuronal activity on αSyn aggregation and spreading, as well as dopaminergic neuronal vulnerability, may provide new therapeutic strategies for patients with LB disease (LBD).